The 2011 Elections in Wales and the Role Played by Civil Society - Moya Jones (Revue LISA, 2014)
The constitutional innovations that devolution brought are turning out to be more innovative in Wales than might have been thought. The setting up of the Welsh Assembly was a historic event in that Wales had never in its history had a nationwide body concerned with the affairs of the Principality. The powers of the Welsh Assembly have recently been substantially increased as the Assembly now has primary law-making powers, the same as those of the Scottish Parliament. However, in recent elections, Welsh voters returned a Labour majority to the Senedd in Cardiff Bay. This is in sharp contrast to the UK government, which is controlled by a Conservative-led coalition with the Liberal Democrats, and Scotland which is dominated by the Scottish Nationalist Party. The distinctiveness of politics in Wales is thus becoming more marked. This article attempts to describe and analyse these recent developments with a particular view to the way that civil society is becoming more confident and is making more and more significant contributions to life in Wales.